Existence results for boundary value problems for fractional hybrid differential inclusions - Dhage, Bapurao C.; Ntouyas, Sotiris K. (Topological Methods in Nonlinear Analysis, 2016)
This paper studies existence results for boundary value problems of nonlinear fractional hybrid differential inclusions of quadratic type, by using a fixed point theorem of Dhage [B.C. Dhage, Existence results for neutral functional differential inclusions in Banach algebras, Nonlinear Anal. 64 (2006), 1290-1306].